International classification... - Campos, Astério (Revista de Biblioteconomia de Brasília, 1975)
São analisados os seguintes documentos: INTERNATIONAL CLASSIFICATION. Journal on theory and pratice of universal and special classification systems and thesauri. München: Verlag Dokumentation, 1974--- v. 1. Semestral. WOJCIECHOWSKI, Jerry A., ed. Conceptual basis of the classification of knowledge. Proceedings of the Ottawa Conference on the Conceptual Basis of the Classification of Knowledge, October 1st to 5th, 1971. München: Verlag Dokumentation, 1974. 503 p. THIRD INTERNATIONAL STUDY CONFERENCE ON CLASSIFICATION RESEARCH, Bombay, 6-11 January, 1975. Trabalhos apresentados. VICKERY, B. C. Classification and indexing in science. 3.ed. London: Butterworths, 1975. 228 p. ISBN 0 408 70662 7. MALTBY, Arthur. Sayer’s manual of classification for librarians. 5.ed. London: André Deutsch, 1975. 336 p. ISBN 0 233 96603 X.